Odpowiedź :
Odpowiedź:
a)
4x(6x² - 5x + 8) = 4x³ - 20x² + 32x
b)
-3a²(a^5 + 5a² - 6) = -3a^7 - 15a^4 + 18a²
c)
(1/4k + 1/2m - 1/16) * 8km = 2k²m + 4km² - 1/2km
d)
(-10q^4 + 15q^5 + 20q^6) * (-0,1q³) = q^7 - 1,5q^8 - 2q^9
e)
-1/3(-3y² - y + 9) * y = y³ + 1/3y² - 3y
f)
-p(-q - 4p + 6pq) * q² = pq³ + 4p²q² - 6p²q³
g)
(60x - 40y + 100) * 0,01xy = 0,6x²y - 4xy² + xy
h)
a(10a - 5b + 15c) * (0,02bc) = 0,2a²bc - 0,1ab²c + 0,3abc²
Szczegółowe wyjaśnienie:
Wydaje mi się, że to tak trzeba było zrobić. Odpowiedź masz w załączniku